Transcriptional response to VZV infection is modulated by RNA polymerase III in lung epithelial cell lines - Doratt, Brianna M.; Vance, Elizabeth; Malherbe, Delphine C.; Ebbert, Mark T.W.; Messaoudi, Ilhem (Frontiers in Cellular and Infection Microbiology, 2022)
Short interspersed nuclear elements (SINEs) are retrotransposons that generate exclusively double-stranded noncoding RNAs transcribed by the ancestral RNA polymerase III (Pol III), a multi-subunit cytosolic polymerase. Although SINE ncRNAs are generally transcriptionally repressed, they can be induced in response to viral infections and can stimulate immune signaling pathways. Indeed, mutations in Pol III have been associated with poor antiviral interferon response following infection with varicella zoster virus (VZV). In this study, we probed the role of Pol III transcripts in the detection and initial immune response to VZV by characterizing the transcriptional response following VZV infection of wild type A549 lung epithelial cells as well as A549 cells lacking specific RNA sensors MAVS, or interferon-stimulated genes RNase L and PKR in presence or absence of functional Polymerase III. Multiple components of the antiviral sensing and interferon signaling pathways were involved in restricting VZV replication in lung epithelial cells thus suggesting an innate defense system with built-in redundancy. In addition, RNase L deficiency led to a unique transcription profile indicating that SINE ncRNAs can act as immune sensors of VZV infection. Collectively, these findings suggest an essential role for Pol III in the antiviral response to VZV infection.